Les arts du spectacle selon les romantiques. Stendhal, Gautier, Nerval critiques musicaux - Opiela-Mrozik, Anna (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2019)
This article is the review of some critical articles of Stendhal, Gautier and Nerval which contain reports of operas, ballets and instrumental music concerts. The aim of this comparative analysis is to define the individual concepts of music and artist. The critics make their own ideal of music through the descriptions of the librettos, scenography and the abilities of the performers. The Stendhal’s remarks from Notes d’un Dilettante resulted from the idea of the modern beauty whereas the Gautier’s articles collected in Histoire de l’art dramatique… show the poet who is sensitive to the visual aspect of a performance and the critic who is open to the newness and dreaming of the harmony in art. Instead, in the Nerval’s press columns are visible the admiration for the music of the past age as well as the interest in the innovative schemes and the idea of the synthetic work which heralds the future art.